Use of antidepressants in a modern globalized society - Tanum, L.; Haslemo, T. (Die Psychiatrie, 2010)
Depression is a highly prevalent condition throughout the world. Ethnicity is reported to influence treatment outcome with antidepressants in a number of ways, including both cultural and genetic factors. Non-genetic factors such as the type of diet, beliefs about depression and attitudes towards treatment with antidepressants are proposed to directly influence medication adherence and the rate of remission. Genetic factors are mainly expressed through inter-individual variance in drug metabolism and must be born in mind when antidepressants are prescribed in a multi-ethnic society. Recent advances in molecular biology have revealed substantial variance in the Cytochrome-P450 enzyme system, which is considered to be the most important and relevant factor for ethnic variance in the metabolism. This underscores the usefulness of therapeutic drug monitoring and individualization of treatment in clinical practice. This paper will briefly review factors related to ethnicity that may be of potential importance for treatment outcome and with a special emphasis on the ethnical diversity of cytochrome P-450 enzyme systems.
Keywords: Psychopharmacology; antidepressants; Cytochrome P 450 enzyme system; depression; ethnicity